Crypto exchanges and credit risk: Modeling and forecasting the probability of closure - Dean Fantazzini; Raffaella Calabrese (Journal of Risk and Financial Management, 2021)
While there is increasing interest in crypto assets, the credit risk of these exchanges is still relatively unexplored. To fill this gap, we considered a unique dataset of 144 exchanges, active from the first quarter of 2018 to the first quarter of 2021. We analyzed the determinants surrounding the decision to close an exchange using credit scoring and machine learning techniques. Cybersecurity grades, having a public developer team, the age of the exchange, and the number of available traded cryptocurrencies are the main significant covariates across different model specifications. Both in-sample and out-of-sample analyzes confirm these findings. These results are robust in regard to the inclusion of additional variables, considering the country of registration of these exchanges and whether they are centralized or decentralized.
Keywords: C21; C35; C51; C53; G23; G32; G33; 330; exchange; Bitcoin; crypto assets; cryptocurrencies; credit risk; bankruptcy; default probability